Incident risk factors as predictors of HIV seroconversion in the Lisbon cohort of men who have sex with men: first results, 2011-2014 - Meireles, P (2015)
HIV incidence in men who have sex with men (MSM) is increasing in western countries, including Portugal. We aimed to estimate HIV incidence and to assess how individual short-term changes in exposures over time predict seroconversion. We evaluated participants of an open cohort of HIV-negative MSM enrolled after testing at a community-based voluntary HIV counselling and testing centre in Lisbon. At each evaluation a structured questionnaire was completed and HIV status was ascertained using rapid followed by confirmatory testing. Between April 2011 and February 2014, 804 MSM were followed for a total of 893 person-years. Predictors of HIV seroconversion were identified using Poisson generalised linear regression. The overall seroincidence was 2.80/100 person-years (95% confidence interval: 1.89–4.14). Men who seroconverted had a higher mean number of tests per year. Seroconversions were significantly associated with partner disclosure of HIV status during follow-up, newly-adopted unprotected anal intercourse (UAI) with a steady partner and being newly-diagnosed with syphilis during follow-up. Likewise, sexual intercourse with HIV-positive men, having an HIV-positive steady partner at least once during follow-up and persistent UAI with occasional partners were predictors of seroconversion. High HIV incidence in this cohort is likely driven by short-term contextual and behavioural changes during follow-up.